(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
In Rajmahal Basin the Upper Gondwana (Mesozoic) sequences are represented by the Dubrajpur and Rajmahal Formations. Palynologically, the Dubrajpur Formation is shown to be a time transgressive unit spanning from Early Triassic to Early Cretaceous. Out of seven palynological assemblages recorded from this formation four have Early Jurassic to Early Cretaceous age. Arcuatipollenites tethyensis Assemblage Zone represents the Late Triassic to Early Jurassic time interval. Callialasporites turbatus Assemblage Zone registers presence of dinoflagellate taxon Phallocysta indicating Late Early to Early Middle Jurassic age. The Contignisporites cooksonii Assemblage Zone has Late Middle Jurassic age. The topmost Ruffordiaspora australiensis Assemblage Zone represents Late Jurassic - Early Cretaceous age. The palynological information from Rajmahal Basin evidently reveals presence of nonmarine Jurassic sediments on Indian peninsula, on the contrary to the old assumption of their absence.